Artificial Ground Freezing Impact on Shear Strength and Microstructure of Granite Residual Soil Under an Extremely Low Temperature - An, Ran; Zhang, Xianwei; Kong, Lingwei; Gong, Jianwu; Lei, Xuewen (Frontiers in Earth Science, 2021)
The Artificial Ground Freezing (AGF) method, which is widely used in tunnel excavations, significantly affects the properties of geotechnical materials in frozen walls under extremely low temperatures. In order to simulate the AGF process, the freezing treatment with a temperature of −30°C and thawing treatment temperature of 25°C were performed on natural specimens of granite residual soil (GRS). Subsequently, triaxial (TRX) tests were conducted to evaluate mechanical properties and Nuclear Magnetic Resonance Image (NMRI) tests were applied to detect pore distributions of GRS. To clarify variations of microstructure after freezing-thawing, the relaxation time (T2) distribution curves and T2-weighted images from NMRI results were thoroughly analyzed from the perspective of quantization and visualization. Results show that the shear strength as well as the cohesion of GRS are reduced sharply by the AGF process, while the internal friction angle decreases gently. The pore size distribution (PSD) converted from the T2 curve is constituted of two different peaks, corresponding to micro-pores with diameters from 0.1 to 10 µm and macro-pores with diameters from 10 to 1,000 µm. Under the AGF impact, the expansion in macro-pores and shrinkage in micro-pores simultaneously exist in the specimen, which was verified from a visualized perspective by T2-weighted images. The frost heaving damage on shear strength is attributed to the microstructural disturbance caused by the presence of large-scale pores and uneven deformations in GRS, which is subjected to the AGF impact under an extremely low temperature.